Risk Factors Associated with Underweight Children Under the Age of Five in Putrajaya, Malaysia: A Case-Control Study - Salleh, Ruhaya; Ahmad, Mohamad Hasnan; Man, Cheong Siew; Wong, Norazizah Ibrahim; Sallehuddin, Syafinaz Mohd; Palaniveloo, Lalitha; Che Abdul Rahim, Norsyamlina; Baharudin, Azli; Abu Saad, Hazizi; Omar, Mohd Azahadi; Ahmad, Noor Ani (Jurnal Gizi dan Pangan, 2023)
The study aimed to determine the associated factors for underweight among children under five years old in Putrajaya, Malaysia. This was a case-control study with a one-to-one ratio matched by sex as well as by three age categories (6‒11 months, 12‒35 months, dan 36‒59 months) between underweight and normal-weight children. There were 364 underweight children and 364 children with normal weight recruited from four government clinics and 118 preschools in Putrajaya. Both groups were assessed via face-to-face interviews; anthropometric measurements; haemoglobin level through finger prick blood sample; and a self-administered 3-day food diary. Underweight is defined as a weight-for-age z score less than -2SD based on World Health Organization (WHO) 2006 Growth Chart. The logistic regression’s final model revealed that various factors were significantly associated with underweight among children under five in Putrajaya. These factors included father being employed as a non-government servant [aOR:1.45 (95% CI:1.04‒2.02) compared to government servant], children from B40 group with a monthly household income less than <RM 7,380 (USD 1727.33) [aOR:2.17 (95% CI:1.01‒4.66) compared to T20], monthly expenditure for childcare less than RM 1,000 (USD 234.06), [aOR:1.77 (95% CI:1.01‒3.10) compared to ≥RM 2,000], underweight mother during prepregnancy [aOR:1.89 (95% CI:1.10‒3.26)] compared to normal weight, anemic children [aOR:1.57 (95% CI:1.15‒2.16)] compared to normal children, children using pacifiers [aOR:1.75 (95% CI:1.21‒2.73)] compared to not using pacifiers and children staying with unregistered babysitters [aOR:2.33 (85% CI:1.52‒3.59)] compared to those attending kindergarten. The above findings suggest several factors are significantly associated with underweight among children under five years old. Therefore, it highlights on the importance of improving household socioeconomic status, maternal nutritional status, and infant and young child feeding practices to prevent underweight issues in this population.